Situational coupling at the ruck and its effects on phase momentum and success in international men`s and women`s rugby sevens - Barkell, J. F.; O'Connor, D.; Cotton, W. G. (Journal of Human Sport & Exercise, 2017)
One of the most frequent contests for possession associated with rugby sevens is the ruck. There has been no research on the patterns of rucks in rugby sevens. The aim of this study was to examine the link between coupling at the ruck, team momentum and success. Footage from all men`s (N=63) and women`s (N=35) IRB Sevens World Series Cup knockout matches played during 2014 were analysed. Situational coupling at the ruck was divided into four categories based on the location of players. These were wide rucks (4&0); mid to wide rucks (3&1); mid rucks (2&2) and foiled rucks for all other situations. Comparisons between winning and losing teams were examined. Winning women`s teams crossed the advantage line resulting in positive momentum significantly more than losing teams (W 64.37% v L 49.59%). Situational analysis identified that wide rucks were most commonly used. Winning women created significantly more positive momentum from wide rucks (W 59.49% v L 42.36%) and scored more tries from wide rucks (W 0.91 v L 0.26) and mid rucks (W 0.53 v L 0.2). Winning men showed that attacking from mid rucks led to positive momentum (W 79.17% v L 54.6%). Winners also scored significantly more tries from wide rucks (W 0.69 v L 0.39). Positive momentum is associated with three or more passes in men`s rugby sevens and four or more passes in women`s rugby sevens. Momentum has been shown to be an important aspect of success in rugby evens. Situational analysis has identified that wide rucks are most commonly used and winning women use wide rucks whilst winning men use mid rucks to gain positive momentum. This study may assist coaches in developing strategies for creating positive momentum in rugby sevens.